2021
DOI: 10.1080/10942912.2020.1861007
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and in-vitro digestibility studies of microwave assisted chemically modified breadfruit (Artocarpus altilis) starch

Abstract: Chemical modifications (citrification, acetylation and phosphorylation) of breadfruit (Artocarpus altilis) starch were performed using dual (microwaveassisted and chemical) processes, the physicochemical properties, degree of substitution and in-vitro starch hydrolysis of the modified starches were evaluated using standard methods while changes in molecular structure was assessed using Fourier transform-infrared (FTIR) spectroscopy. The results showed that bulk density ranged from 0.22 to 0.28 g/ml, swelling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
8
0
5
Order By: Relevance
“…On the contrary, HBSI and HBSP showed relatively wider bandwidths than HBS, suggesting a higher crystallite structure [ 19 ]. It was noteworthy that the representative peak of -OH was found to be around 3370.0 cm −1 , whereas the microwave-assisted autoclaving and isoamylase debranching modifications led to apparent redshifts with the absorption changed to 3392.0 cm −1 , representing a substitution of the O-H bound [ 28 ]. No evident impacts on the -OH peak were found in HBSA and HBSP.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, HBSI and HBSP showed relatively wider bandwidths than HBS, suggesting a higher crystallite structure [ 19 ]. It was noteworthy that the representative peak of -OH was found to be around 3370.0 cm −1 , whereas the microwave-assisted autoclaving and isoamylase debranching modifications led to apparent redshifts with the absorption changed to 3392.0 cm −1 , representing a substitution of the O-H bound [ 28 ]. No evident impacts on the -OH peak were found in HBSA and HBSP.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation increases starch solubility by retaining water molecules due to the higher affinity of substituent groups for water in the starch granules 33 . Many authors have reported the increase in solubility of acetylated starches 17,34,35 . It is believed that acetyl groups in starch could disrupt hydrogen bonding in the granules and disorganize the intragranular structure, making it easier for water to reach the amorphous regions of the acetylated starches 18 …”
Section: Resultsmentioning
confidence: 99%
“…In vitro starch digestibility of MCF was analysed by measuring the maltose level as the product of hydrolysis MCF by using α-amylase from Aspergillus oryzae (Sigma 10065-10G) 100 U compared to starch solution. This analysis was performed by referring to a method from Otemuyiwa and Aina (2021) . Sample absorbance and blank solution were determined by Spectrophotometer UV-Vis (Shimadzu UV-1800, Tokyo, Japan) at 520 nm.…”
Section: Methodsmentioning
confidence: 99%